Robertson Stephens Daily Growth Stock Update on ELNT JNPR PDYN PMCS SONS VTSS IECIF CBIS RSAS STMP BBSW (PR Newswire, 2000)
Robertson Stephens maintains a market in the shares of Paradyne; Juniper Networks, Inc.; C-Bridge Internet Solutions; PMC-Sierra, Inc.; RSA Security, Inc.; Vitesse Semiconductor; Intershop; Broadbase; Sonus Networks; Stamps.com, Elantec Semiconductors and Keynote Systems and has been a comanaging underwriter for or has privately placed securities of Paradyne; Juniper Networks, Inc.; C- Bridge Internet Solutions; PMC-Sierra; RSA Security, Inc.; Sonus Networks; Stamps.com and Keynote Systems within the past three years. Robertson Stephens is the leading full-service investment bank focused exclusively on growth companies. The market leader in technology IPOs, Robertson Stephens completed 103 deals in the US and Europe in the first quarter of 2000, valued at $40 billion, including 103 IPOs, follow-ons and convertibles. In addition, the firm completed 32 private placements in the first quarter and 37 M&A deals. In 1999, the firm completed 384 transactions, valued at $100 billion, including 233 IPOs, follow-ons and convertibles, 66 private placements and 85 M&A deals. The firm's 47 equity research analysts cover nearly 700 companies. Founded in 1978, Robertson Stephens (Legal name: FleetBoston Robertson Stephens Inc.) is a section 20 subsidiary of FleetBoston Financial Corporation (NYSE: FBF) and a member of the NASD and all major exchanges. Together, Robertson Stephens, FleetBoston Robertson Stephens International Ltd., and Robertson Stephens Evergreen Securities Ltd. has over 1,200 employees worldwide with offices in Boston, San Francisco, New York, Menlo Park, Chicago, Atlanta, London, Munich and Tel Aviv. The information contained herein is not a complete analysis of every material fact respecting any company, industry or security. Although opinions and estimates expressed herein reflect the current judgment of FleetBoston Robertson Stephens Inc., the information upon which such opinions and estimates are based is not necessarily updated on a regular basis; when it is, the date of the change in estimate will be noted. In addition, opinions and estimates are subject to change without notice. This Report contains forward- looking statements, which involve risks and uncertainties. Actual results may differ significantly from the results described in the forward-looking statements. Factors that might cause such a difference include, but are not limited to, those discussed in "Investment Risks." FleetBoston Robertson Stephens Inc. from time to time performs corporate finance or other services for some companies described herein and may occasionally possess material, nonpublic information regarding such companies. This information is not used in the preparation of the opinions and estimates herein. While the information contained in this Report and the opinions contained herein are based on sources believed to be reliable, FleetBoston Robertson Stephens Inc. has not independently verified the facts, assumptions and estimates contained in this Report. Accordingly, no representation or warranty, expressed or implied, is made as to, and no reliance should be placed on, the fairness, accuracy, completeness or correctness of the information and opinions contained in this Report. FleetBoston Robertson Stephens Inc., its managing directors, its affiliates, and/or its employees may have an interest in the securities of the issue(s) described and may make purchases or sales while this report is in circulation. FleetBoston Robertson Stephens International Ltd. is regulated by the Securities and Futures Authority in the United Kingdom. This publication is not meant for private customers.